The white tiger - Adiga, Aravind 1974- (Atlantic Books, 2008)
Balram Halwai is a complicated man. Servant. Philosopher. Entrepreneur. Murderer. Over the course of seven nights, by the scattered light of a preposterous chandelier, Balram tells the terrible and transfixing story of how he came to be a success in life -- having nothing but his own wits to help him along.
Keywords: Geschichte 1900-2007; Ambition -- Fiction; Businesspeople -- India -- Bangalore -- Fiction; Chauffeurs -- India -- Bangalore -- Fiction; Poor -- India -- Bangalore -- Fiction; Englisch; Roman; Indien; Bangalore (India) -- Social conditions -- Fiction; Fiktionale Darstellung; Text